THE POSITION OF THE GERMAN ACCOUNTANT. - Matz, A. (The Accounting Review, 1938)
Abstract From September 19-24, 1938, occurred the Fifth International Congress on Accounting in Berlin, Germany, which brought together German accountants and trustees, and representatives from appropriately forty foreign nations. This convention was again the occasion for discussions on the real status of the accounting profession within the new national pattern. To indicate the position of the German accountant is the object of this paper. The last five years have brought an abrupt about-face in political, cultural, social, economic and professional Thinking in Germany. No phase of national life has remained untouched. Because the efforts and endeavors of every individual are first to serve the welfare of all the people, the education of the individual to the ideology of National Socialism is a most necessary prerequisite. While alignment to the new pattern was accomplished very quickly in many fields, the professional occupations remained aloof from the new mode of thought; but now, with the aid of legal and educational forces, they, too, are following the trend. Among the professions, the accountant, whether private or public, has always occupied an honorable and important position.